2019
DOI: 10.1038/s41598-019-52337-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and phylogenetic implications of the complete mitochondrial genome of Ledra auditura

Abstract: We sequenced and annotated the first complete mitochondrial genome (mitogenome) of Ledra auditura (Hemiptera: Cicadellidae: Ledrinae) and reconstructed phylogenetic relationships among 47 species (including 2 outgroup species) on the basis of 3 datasets using maximum likelihood (ML) and Bayesian inference (BI) analyses. The complete L. auditura mitogenome (length, 16,094 bp) comprises 37 genes [13 protein-coding genes (PCGs), 22 tRNAs, and 2 rRNAs], 1 control region, and 2 long non-coding regions. The first lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 47 publications
17
24
1
Order By: Relevance
“…This result supported that treehoppers were derived from paraphyletic Cicadellidae, which has been proven in previous studies (Dietrich et al, 2001(Dietrich et al, , 2017Zhao and Liang, 2016;Du et al, 2017a,b;Du Y. et al, 2019;Skinner et al, 2019). As previously reported by Wang et al (2019a) Ledrinae was found to be the sister group of all leafhoppers and treehoppers present in our trees. Unfortunately, the relationships of Macropsinae have not been fully resolved in this study.…”
Section: Phylogenetic Analysessupporting
confidence: 93%
See 1 more Smart Citation
“…This result supported that treehoppers were derived from paraphyletic Cicadellidae, which has been proven in previous studies (Dietrich et al, 2001(Dietrich et al, , 2017Zhao and Liang, 2016;Du et al, 2017a,b;Du Y. et al, 2019;Skinner et al, 2019). As previously reported by Wang et al (2019a) Ledrinae was found to be the sister group of all leafhoppers and treehoppers present in our trees. Unfortunately, the relationships of Macropsinae have not been fully resolved in this study.…”
Section: Phylogenetic Analysessupporting
confidence: 93%
“…The locations of two rRNA genes (16S rRNA and 12S rRNA) were determined by comparing the homologous sequences with previously published mitochondrial sequences for the members of Hemiptera in GenBank. Secondary structures of rRNA genes were predicted based on previously reported models (Wang et al, 2017a(Wang et al, , 2019a variable regions of the elements were predicted using DNASIS version 2.5 (Hitachi Engineering, Tokyo, Japan) and RNA Structure (v 5.2) (Reuter and Mathews, 2010). We calculated strand asymmetry using the formulas: AT skew = (A − T)/(A + T) and GC skew = (G − C)/(G + C) (Perna and Kocher, 1995).…”
Section: Sequence Assembly Annotation and Analysismentioning
confidence: 99%
“…Our putative ingroup was recovered as monophyletic with respect to Cicadoidea and Cercopoidea. The inferred relationships based on the PCG123 and AA datasets Iassinae + Coelidiinae are sister to a clade comprising Megophthalminae and treehoppers with moderate to high values, which is consistent with previous phylogenetic analyses [34,42,43]. For the PCG12R datasets, Iassinae + Coelidiinae and Deltocephalinae are grouped into a clade.…”
Section: Phylogenetic Relationshipssupporting
confidence: 88%
“…The mtgenomes of P. chlorophana and T. sagittata were 14,927 bp and 14,918 bp long, respectively ( Figure 1 ). Among the four complete mitogenomes of Ledrinae, T. sagittata has the smallest mtgenome of 14,198 bp, while L. auditura contains the largest at 16,094 bp due to two long non-coding regions [ 30 ]. This finding was comparable to the sequence lengths found for other reported Ledrinae mtgenomes [ 8 , 30 ].…”
Section: Resultsmentioning
confidence: 99%